Pemodelan Konverter AC – DC Tiga Fasa Dua Arah Pada Sepeda Listrik Menggunakan Metode SPWM - Hellga Afdilah Putri; Amir Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This study is aimed to design and analyze bidirectional converter three phase by using method SPWM on electric bike. This study discusses the three-phase inverter with Sine Pulse WidthModulation (SPWM) method as a three-phase induction motor drive and also the rectifier which has function to convert the AC voltage of the source of three-phase AC into DC voltage that ismodeled by using Matlab / Simulink. The purpose of this study is to get the design of the threephase inverter SPWM as a three-phase induction motor drive 500 W, 30 V, and 50 Hz. Theinverter design using battery voltage 48 V. Besides that to getting rectifier mode design that is aimed to fill a 48 Volt DC battery that is a driving source an induction machine when that isnot driven from PLN. The results of the analysis inverter mode performed on the motor no-load conditions (zero load). Through simulation with Matlab software is then obtained curve ofsinusoidal voltage box 48 Volt, current 2,5 Ampere, and speed of the motor by SPWM controlled system. Then, the simulation results in rectifier mode is done with Matlab software value obtained 52.03 Volt battery charging voltage and battery charging current is 7.977 Amperes.Keyword : Three Phase Inverter, Sine Pulse Width Modulation (SPWM), Three Phase Induction Motor, Matlab/ Simulink, Electric bike, Rectifier.